Hope, agency, and adolescents' sexual and reproductive health: A mini review - Groenewald, Candice; Isaacs, Nazeema; Qoza, Phiwokazi (Frontiers in Reproductive Health, 2023)
Availability of and access to services that promote sexual and reproductive health (SRH) amongst adolescent girls have become a global priority. Yet, while researchers have explored factors that influence the uptake of SRH services in low-and-middle income countries, the roles that “agency” and “hope” play in adolescent SRH is less understood. To study this, this mini review systematically reviewed the literature across three databases, EBSCO-host web, Pubmed and South Africa (SA) epublications, for the period of January 2012 to January 2022. Findings showed that a paucity of studies identified the link between agency, hope and adolescent SRH respectively. Our review included 12 articles and found no studies that focused on hope and its role in adolescent SRH or seeking SRH services. However, the literature revealed the complexities of adolescent SRH agency and autonomy where female adolescents had limited autonomy to make SRH decisions. Limited access to adolescent friendly SRH services was also found to restrict girls' agency to prevent unintended pregnancies or to take up SRH support. Given the paucity of research, empirical studies are needed to further understand the extent to which hope, agency and other subjective factors implicate adolescent SRH in the African context.